Nitrogen mineralization pattern of agroforestry tree leaves under tropical highland conditions - Anthofer, J.; Hanson, Jean; Jutzi, S.C. (Wiley, 1997)
Leaves of nine agroforestry tree species (Grevillea robusta, Erythrina abyssinica, Gliricidia sepium, Albizia schimperiana. Acacia nilotica. Acacia polyacantha, Leu-caena leucocephala, Leucaena pallida and Entada abys-sinica) were compared in a glasshouse incubation experiment under natural temperature conditions to relate the observed nitrogen mineralization pattern to quality factors of the mulch material such as N, lignin, phenolic and tannin content and C/N ratio, lignin/N ratio, phenolic/N ratio and (lignin -I- phenolics)/N ratio. Separation of the plant material into leaflets and petioles/rachis or into leaves and petioles with subsequent chemical analyses revealed large differences in the quality of the material not only between species but also amongst plant parts within the same species. Erythrina abyssinica, G. sepium, L. leucocephala and L. pallida had a rapid nitrogen release especially during the early sampling dates and were superior compared with mulch treatments of G. robusta, A. polyacantha, and Entada abyssinica. Immobilization processes started around 5 weeks after incubation and continued up to the end of the experiment, 9 weeks after incubation. N and lignin content, C/N ratio, lignin/N ratio, phenolics/N ratio and (phenolics + lignin)/N ratio were all significantly correlated with mineralized nitrogen after 3 weeks but their influence in driving the mineralization pattern decreased with incubation time.